2016
DOI: 10.2527/jas.2015-0181
|View full text |Cite
|
Sign up to set email alerts
|

Postrigor citric acid enhancement can alter cooked color but not fresh color of dark-cutting beef1

Abstract: In 2 experiments, dark-cutting (DC) beef strip loins were used to test the effects of citric acid-enhancement pH on visual and instrumental color of fresh and cooked steaks. In Exp. 1 and 2, each DC (mean pH = 6.57 and 6.65, respectively) and normal-pH, low USDA Choice (CH; mean pH = 5.48 and 5.51, respectively) strip loin was cut into 2 equal-length sections, and DC sections were injected to 111% of raw section weight with pH 3.5 to 5.0 (Exp. 1) or pH 2.0 to 3.5 (Exp. 2) solutions made by mixing citric acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Seyfert et al (2007) noted that ground beef treated with water presented a lighter and brighter red color (Seyfert et al, 2007). Previous research reported that the citric and lactic acid enhancement increased free-water in dark-cutting steaks (Sawyer et al, 2009;Stackhouse et al, 2016). Further, the addition of water in meat through enhancement can have a slight effect on pH (Hamm, 1961).…”
Section: Effects Of Aging Antioxidants Packaging and Display Time mentioning
confidence: 97%
See 1 more Smart Citation
“…Seyfert et al (2007) noted that ground beef treated with water presented a lighter and brighter red color (Seyfert et al, 2007). Previous research reported that the citric and lactic acid enhancement increased free-water in dark-cutting steaks (Sawyer et al, 2009;Stackhouse et al, 2016). Further, the addition of water in meat through enhancement can have a slight effect on pH (Hamm, 1961).…”
Section: Effects Of Aging Antioxidants Packaging and Display Time mentioning
confidence: 97%
“…A greater ultimate muscle pH shifts the pH away from the isoelectric point; hence, muscle fibers can hold more water resulting in muscle fiber swelling and less free water on the surface to reflect light (Barbut et al, 2005;Swatland, 2008). Dark-cutting steaks have greater levels of bound water and less free water than normal pH steaks (Sawyer et al, 2009;Stackhouse et al, 2016). In support, approximately 60% less overall reflectance was noted in dark-cutting steaks than normal-pH steaks (English et al, 2016a).…”
Section: Effects Of Aging Antioxidants Packaging and Display Time mentioning
confidence: 99%
“…The least MMb formed in MRA analysis in high pHu group is in concordance with other findings in this study, such as higher redness (more a* and a*/b*) and lower discoloration throughout storage (less Hue and surface MMb), It demonstrates the oxidative protection of high pHu regarding red color stability, as authors have been documented (ABRIL et al, 2001;CHMIEL et al, 2012;ENGLISH et al, 2016;GEORGE;STRATMANN, 1952;MCKEITH et al, 2016;STACKHOUSE et al, 2016;WULF;WISE, 1999 The greater content of NADH in the high pHu group could also be a factor for the increased MRA this group had in this study.…”
Section: Surface Pigmentssupporting
confidence: 92%
“…Other authors showed decreased hue and Chroma as pH u increased and (ABRIL et al, 2001;MCKEITH et al, 2016;STACKHOUSE et al, 2016;WȨGLARZ, 2010). Lower Chroma indicates that as pH u increases, surface color presents less vivid, losing normal pH u bright red color, which may be attributable to higher OCR.…”
Section: The Effect Of Ph U On Meat Colormentioning
confidence: 87%
See 1 more Smart Citation